Evaluation of energy efficiency of PEM type fuel cell - Mróz, Tomasz; Sinacka, Joanna; Fórmaniak, Kacper (Instal, 2025)
Cogenerated heat and power production on a large scale is widely known and is used in industry (industrial combined heat and power plants), municipal heating systems and public utility buildings (hospitals, office buildings). However, the application of this technology on a smaller scale is rarely implemented due to high investment costs and a poorly developed market for such equipment. Significantly lower non-renewable primary energy factor for heat production in cogeneration systems compared to traditional heating systems (boilers and heating plants), makes it possible to meet the goals of the Green Deal in terms of increasing building energy efficiency. The article presents the results of energy efficiency evaluation of 1,1 kW heating capacity and 0,75 kW electrical power the PEM-type fuel cell powered by natural gas. The operating cycle of the fuel cell is 48 hours: 46 hours of device operation followed by a 2-hour of technological break for necessary regeneration. Measurements of cooling water flow and temperatures, natural gas consumption and electricity production allowed for derivation of daily average energy efficiency and nonrenewable primary energy effort factor of tested the fuel cell. It has been found that during the study period, the average energy efficiency and a non-renewable primary energy effort factor of the fuel cell tested have been 82.1% and 0.319 respectively, highlighting the attractiveness of using such a device as the energy source in single-family residential buildings.
Keywords: energy efficiency; PEM type fuel cell